The interaction of affective with psychotic processes: A test of the effects of worrying on working memory, jumping to conclusions, and anomalies of experience in patients with persecutory delusions - Freeman, D; Startup, H; Dunn, G; Cernis, E; Wingham, G; Pugh, K; Cordwell, J; Kingdon, D (Elsevier, 2013)
Worry has traditionally been considered in the study of common emotional disorders such as anxiety and depression, but recent studies indicate that worry may be a causal factor in the occurrence and persistence of persecutory delusions. The effect of worry on processes traditionally associated with psychosis has not been tested. The aim of the study was to examine the short-term effects of a bout of worry on three cognitive processes typically considered markers of psychosis: working memory, jumping to conclusions, and anomalous internal experience. Sixty-seven patients with persecutory delusions in the context of a non-affective psychotic disorder were randomised to a worry induction, a worry reduction, or a neutral control condition. They completed tests of the cognitive processes before and after the randomisation condition. The worry induction procedure led to a significant increase in worry. The induction of worry did not affect working memory or jumping to conclusions, but it did increase a range of mild anomalous experiences including feelings of unreality, perceptual alterations, and temporal disintegration. Worry did not affect the occurrence of hallucinations. The study shows that a period of worry causes a range of subtle odd perceptual disturbances that are known to increase the likelihood of delusions. It demonstrates an interaction between affective and psychotic processes in patients with delusions.